Research progress of treating hyperuricemia in rats and mice with traditional Chinese medicine - Bai, Haodong; Zhang, Zidong; Zhu, Mingtao; Sun, Yanping; Wang, Yimeng; Li, Biao; Wang, Qiuhong; Kuang, Haixue (Frontiers in Pharmacology, 2024)
Hyperuricemia (HUA) is a common chronic metabolic disease caused by abnormal purine metabolism and uric acid excretion. Despite extensive research on HUA, no clear treatment has been found so far. Improving purine metabolism and promoting uric acid excretion is crucial for the effective treatment of HUA. In recent years, traditional Chinese medicine and traditional Chinese medicine prescriptions have shown good effects in treating HUA. This article summarizes the latest progress in treating HUA in rats and mice using traditional Chinese medicine and prescriptions, elaborates on the pathogenesis of HUA, explores the application of commonly used traditional Chinese medicine treatment methods and prescriptions, and discusses the previous pharmacological mechanisms. In general, our research indicates that traditional Chinese medicine can effectively relieve the symptoms related to elevated uric acid levels in HUA rats and mice. However, further exploration and research are needed to verify its efficacy, safety, and feasibility.